Single-language and code-switching strategies in immigrant and heritage varieties: Spanish subject personal pronouns in Toribio's cross-modal hypothesis - OTHEGUY, RICARDO (Bilingualism (Cambridge, England), 2004)
In an important theoretical contribution to our understanding of language contact, Toribio elaborates on the familiar generalization, best known from the work of Silva-Corvalán, that contact varieties resemble monolingual lects of the same language in overall grammar, but differ with regard to (a) the selection of structures and (b) the semantic-pragmatic constraints on the use of structures. In Toribio's valuable elaboration of this basic idea, these peculiar patterns of selection and constraint in the contact variety are not the same in all contexts of use, but differ depending on whether the bilingual is in the single-language mode, or in the codeswitching mode where stretches of speech in the contact variety alternate, rapidly and relatively seamlessly, with stretches in the acrolect. The insight is that the same type of process that distinguishes the contact variety from its monolingual reference lects also distinguishes, within the contact variety, the codeswitching mode from its single-language reference mode.